The revised formal social support for autonomy and dependence in pain inventory (FSSADI_PAIN): confirmatory factor analysis and validity - Matos, M. (2015)
ain among older adults is common and generally associated with high levels of functional disability. Despite its important role in elders' pain experiences, perceived (formal) social support (PSS) has shown inconsistent effects on their functional autonomy. This suggests a moderator role of 2 recently conceptualized functions of PSS: perceived promotion of dependence versus autonomy. The present study aimed at revising and further validating the Formal Social Support for Autonomy and Dependence in Pain Inventory (FSSADI_PAIN), which measures these 2 PSS functions among institutionalized elders in pain. Two hundred fifty older adults (mean age = 81.36 years, 75.2% women) completed the revised FSSADI_PAIN along with measures of physical functioning (ie, Medical Outcome Study Short Form-36) and informal PSS (ie, Social Support Scale of Medical Outcomes Study). Confirmatory factor analyses showed a good fit for a 2-factor structure: 1) perceived promotion of autonomy (n = 4 items; alpha = .89), and 2) perceived promotion of dependence (n = 4 items; alpha = .85). The revised FSSADI_PAIN showed good content, discriminant, and criterion-related validity; it discriminated the PSS of male and female older adults and also of elders with different levels of physical functioning. In conclusion, the revised FSSADI_PAIN is an innovative, valid, and reliable tool that allows us to assess 2 important functions of PSS, which may play a relevant role in the prevention and reduction of pain-related physical disability and functional dependence among institutionalized older adults. Perspective: This article presents a revised version of the FSSADI_PAIN that assesses elders' perceived promotion of functional autonomy/dependence as 2 independent functions of perceived social support. This measure may contribute to future research on the role of close interpersonal contexts on the promotion of active aging among elders with chronic pain.